SOCIAL AND RELIGIOUS CONSTRUCTION OF HANTA UA PUA TRADITION IN BIMA - Halimi, Halimi; Ulya, Uzmatul (Annual International Conferences on Language, Literature, and Media, 2023)
The tradition of Hanta UA PUA in Bima to commemorate Muhammad Saw's birthday is not only in the form of religious ritual symbols, but it also accommodates societal values in the preparation and implementation of its traditions. Therefore, there is a form of integration of religious and social values in the Hanta UA PUA tradition. This study aims to reveal (1) the Construction of religious values in the Hanta UA PUA tradition in Bima and (2) the Construction of social values in the Hanta UA PUA tradition in Bima. This type of research is a qualitative study using the interview method. Interviews were conducted with culturalists in Bima. The results showed that the researchers found the construction of religious values and the construction of community social values contained in the Hanta UA PUA traditional ceremony. The construction of religious values includes those related to Creed, morals, and worship. Meanwhile, constructing social values includes strengthening relationships, social equality, and Cooperation. The construction of social and religious values contained in the Hanta UA PUA customary ceremony was inseparable from the ulama's struggle during Sultan Abdul Khair Sirajuddin (1640-1682 AD) and the enthusiasm of the Bima community in religion and society. Thus, this study shows that the Hanta UA PUA tradition deserves to be preserved and reorganized to appreciate the services of scholars who have broadcast Islam in Bima.